PERANCANGAN E - TRANSAKSI PEMBAYARAN INTERNET SERVICE PROVIDER PADA PT DIGITAL NETWORK ANTANUSA (DNA.NET) KOTA JAMBI - Ade Setiawan Syah; Noneng Marthiawati; Kevin Kurniawansyah (LPPM Universitas Muhammadiyah Jambi, 2024)
PT Digital Network Antanusa (DNA.Net) Jambi City is an internet service provider network service company in the city of Jambi. DNA.Net operates using cable and wireless network technology (wireless). DNA.Net is not a cellular or satellite service, but something new, much better and much faster to connect to the internet and provide to homes or companies. However, there are still problems with processing, paying and checking internet bills, therefore errors and files are often lost when processing payment transaction data. These include frequent errors in internet registration data information and lost documents, delays in transactions or transactions taking too long, and even making payment reports is still not neat. This method used is the UML (Unified Modeling Language) method which describes the system model including use cases, use case specifications, activities and class diagrams and the designs used by researchers are prototypes. Therefore, the researcher aims to analyze and design an internet service provider payment transaction information system so that a computerized payment system is more flexible and efficient so that problems at PT Digital Network Antanusa can be resolved so that the obstacles currently faced can be resolved and run very well. . The final result of the analysis and design produces a maturity system. This is done to make the system more effective and efficient and of course to make the bill payment process easier